IMPLEMENTASI KERJA SAMA INDONESIA-RUSIA BIDANG PERTAHANAN (2018-2022) - Sanira, Helda; Jamaan, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research was conducted to analyze the implementation of Indonesia-Russia cooperation in the defense sector in the 2018-2022. Indonesia-Russia cooperative relations have existed for a long time since the Soekarno administration until now during the Joko Widodo administration, they have been running harmoniously. Starting with meetings, visiting each other and even signing various cooperation contracts, one of which was in the defense sector. Implementation of cooperation between Indonesia and Russia in the defense sector which was signed in 2018 after the issuance of Law no. 7 of 2019 concerning ratification of the Indonesia-Russia cooperation agreement in the defense sector which was officially signed in 2016. The author uses qualitative methods with secondary data sourced from literature studies by searching, reviewing and collecting various information from library sources such as books, scientific journals, official statements, various kinds of official reports from both government and non-government bodies. , as well as newspapers and news from mass media, both print and electronic. This study uses the Theory of Defense Cooperation at the level of nation-state analysis. The results of this research show that the defense cooperation relationship between Indonesia and Russia in 2018-2022 did not have a significant influence on the arms trade aspect with the absence of exports and imports or interactions between the two countries due to a decline. This is based on several obstacles, including the threat of CAATSA sanctions imposed by the United States, budget funds that were diverted during the Covid-19 pandemic, and obstruction by the Ukrainian war in 2022. Keywords: Defense, Indonesia, Russia, cooperation